Effect of Servo Tomato (Solanum lycopersicum) extract on Incision Wound Healing - Agustina P. Khumara; Henry Y. Mandalas; Vinna K. Sugiaman (e-GiGi, 2022)
Abstract: Herbal medicines such as Servo tomato containing flavonoids and saponins can increase the number of fibroblasts in the wound tissue, therefore, it can help to speed up wound healing time. This study aimed to determine the effect of servo tomato ethanol extract on wound healing time based on the day of the incision. This was a true laboratory experimental study using 30 male Wistar rats (Rattus Norvegicus) divided into six groups; each group consisted of five rats, Group I was given aquadest as a negative control, Group II was given 10% povidone iodine solution as a positive control, and Groups III-VI were given 25%, 50%, 75%, and 100% solutions of Servo tomato ethanol extract, consecutively. The results showed that there were differences in the length of the incision wounds among groups from time to time as a response of wound healing. Incision wound length in Group VI (100%) after seven days had a mean of zero (0.00 mm). The ANOVA test resulted in a p-value of 0.1537 (<0.05) in the six treatment groups. The mean incision length was the shortest in the group applied with 100% Servo tomato ethanol extract. In conclusion, there was an effect of Servo tomato ethanol extract on incision wound healing time on the labial mucosa of male Wistar rats.Keywords: tomato ethanol extract; incision wound; healing timeÂ Abstrak: Tanaman herbal seperti tomat Servo yang mengandung flavonoid dan saponin dapat mening-katkan jumlah fibroblas dalam jaringan luka yang membantu mempercepat waktu penyembuhan luka. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak etanol tomat Servo terhadap waktu penyembuhan luka berdasarkan hari dilakukan insisi. Jenis penelitian ialah eksperimental laboratorik dengan hewan coba tikus Wistar jantan (Rattus norvegicus) berjumlah 30 ekor, dibagi menjadi enam kelompok penelitian; setiap kelompok terdiri dari lima ekor tikus. Kelompok I diberikan larutan aquadest sebagai kontrol negatif, kelompok II diberikan larutan povidone iodine 10% sebagai kontrol positif, dan kelompok III-VI diberikan larutan ekstrak etanol tomat Servo 25%, 50%, 75%, dan 100%. Hasil penelitian mendapatkan perbedaan panjang luka insisi antar kelompok dari waktu ke waktu sebagai respon penyembuhan luka. Panjang luka insisi pada kelompok VI (100%) setelah tujuh hari memiliki rerata nol (0,00 mm). Hasil uji ANOVA mendapatkan nilai p=0,1537<0,05 pada keenam kelompok perlakuan. Jumlah rerata panjang luka insisi paling kecil pada kelompok yang diaplikasikan dengan ekstrak etanol tomat Servo 100%. Simpulan penelitian ini ialah terdapat pengaruh ekstrak etanol tomat Servo (Solanum lycopersicum) terhadap panjang luka selama waktu penyembuhan luka insisi pada mukosa labial tikus Wistar jantan.Kata kunci: ekstrak etanol tomat; luka insisi; waktu penyembuhan